Dispersing upconversion nanocrystals in PMMA microfiber: a novel methodology for temperature sensing. Issue 35 (25th May 2018) - Shahzad, Muhammad Khuram; Zhang, Yundong; Cui, Lugui; Liu, Lu; Butt, Mehwish Khalid; Li, Hanyang
Abstract : The synthesis of a β-NaYF4 :Yb 3+ /Tm 3+ phosphor by a thermal decomposition method, focusing on the fabrication of microfibers by the co-doping of nanocrystals with PMMA solution. Abstract : This paper reports the synthesis of a β-NaYF4 :Yb 3+ /Tm 3+ phosphor by a thermal decomposition method and focuses on the fabrication of microfibers by the co-doping of nanocrystals with PMMA solution via a facile drawing method. The structural characteristics of the nanocrystals are studied by XRD and TEM techniques. Meanwhile, the optical properties of the microfibers are probed by wave guiding performance and upconversion spectroscopy. With the excitation of a 980 nm laser source, the microfiber presented blue upconversion emission of Tm 3+ ions. The fluorescence intensity ratio (FIR) method is utilized for the non-thermally coupling transition ( 1 D2 → 3 F4 (452 nm) and 1 G4 → 3 H6 (476 nm)) levels to carry out the optical thermometry. The maximum sensitivity is recorded at 298 K and is 0.00157 K −1 . The results suggest that the microfibers have potential applications in thermometry with high sensitivity.